Effect of steaming treatment in the structure and reactivity of FCC catalysts - Tonetto, Gabriela Marta (2006)
The shape selectivity properties of USY zeolite crystallites is discussed, and is based on catalyst characterization, molecular simulation, catalytic experiments of model compounds and kinetic modeling. Typical FCC catalysts are prepared with different HY crystallite sizes (0.4 and 0.9 μm), and are structurally and chemically characterized with nitrogen and argon adsorption/desorption isotherms, temperature-programmed desorption of ammonia and infrared spectroscopy. Catalyst characterization is carried out before and after the hydrothermal treatment (steaming) of the catalyst. Pore-size distribution analysis demonstrates that the effect of the steaming treatment in the Y zeolite results in window enlargement. The influences of structural changes of steam treatment on reactivity is evaluated with the catalytic conversion of 1,2,4-trimethylbenzene in a novel fluidized CREC riser simulator. It is proven that steaming enlarges zeolite windows and influence the 1,2,4-TMB product distribution. A slight modification of the window diameter is proven to significantly affect the adsorbent-adsorbate interactions. Focus is particularly given to the catalyst selectivity toward the tetramethylbenzene isomers, and the "transition-state shape selectivity" is proven to be controlling the product distribution and is consistent with molecular mechanics calculations.